Suppression of irradiation defects and crack propagation in niobium via grain boundary engineering: A deep potential molecular dynamics study - Jiahang Li; Yajun Zhang; Jie Wang; Huadong Yong (Materials & Design)
Superconductor niobium has attracted remarkable interest in recent decades due to their superior superconducting and mechanical properties, as well as practical applications in superconducting devices. However, it was inevitably exposed to irradiation fields and micro-crack propagation in extreme operating environments. Therefore, developing precise computational method for precise description of irradiation and micro-crack induced defects and exploring efficient strategy to suppress the accompanied damage become extremely important for the reliable and stable device performance. Here, we developed a multi-scale framework based on first-principles simulations, machine learning potential, and molecular dynamics simulations. The model provides simultaneously accurate description of mechanical parameters, point defect formation energy, grain boundary (GB) energy, and stacking faults energy. Based on this model, we screened out several metastable GBs that should be preferred in practice. Going further, the effect of GB on irradiation damage and micro-crack propagation are systematically investigated. By the proper selection of suitable GB, it is possible to effectively improve the irradiation resistance, strength, and fracture toughness, which are critical for suppressing irradiation damage and micro-crack propagation. These findings significantly extend the current understanding of GB engineering in niobium and provide a solid foundation for the design of high radiation-resistant and fracture toughness polycrystalline niobium.